National Audubon Society field guide to tropical marine fishes of the Caribbean, the Gulf of Mexico, Florida, the Bahamas, and Bermuda - Smith, C. Lavett 1927-2015 (National Audubon Society field guide series, 1997)
Identifica los peces marinos tropicales que viven frente a las costas de América del Norte.